2019
DOI: 10.3390/rs11161943
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Hazard Exposure Mapping Using Machine Learning Techniques: A Case Study from Iran

Abstract: Mountainous areas are highly prone to a variety of nature-triggered disasters, which often cause disabling harm, death, destruction, and damage. In this work, an attempt was made to develop an accurate multi-hazard exposure map for a mountainous area (Asara watershed, Iran), based on state-of-the art machine learning techniques. Hazard modeling for avalanches, rockfalls, and floods was performed using three state-of-the-art models—support vector machine (SVM), boosted regression tree (BRT), and generalized add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 75 publications
1
42
0
1
Order By: Relevance
“…Using AHP, the normalized rate (NR) of the five distance classes were determined (Table 3 ). The exposure map was prepared according to experts’ ratings for different school-vulnerability classes (based on distance from flood hazard zone) 15 , 88 – 90 and the AHP results (Fig. 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using AHP, the normalized rate (NR) of the five distance classes were determined (Table 3 ). The exposure map was prepared according to experts’ ratings for different school-vulnerability classes (based on distance from flood hazard zone) 15 , 88 – 90 and the AHP results (Fig. 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sample was randomly divided into a modeling set containing 70 percent of the locations and a validation set containing 30% of the sample. As flood occurrence is determined by an interaction of natural and human processes, based on previous studies 15 , 53 – 55 12 of the most important effective factors were identified for use in modeling as input variables. They included elevation, slope, aspect, plan curvature, lithology, drainage density, annual rainfall, topographic wetness index (TWI), normalized difference vegetation index (NDVI), land use type, distance from nearest river, and distance from nearest road.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Noticeably, very high precipitation intensity events often occur in the rainy season within a short period, observed in steep slopes, leading to the frequent occurrence of flash floods along with landslides in the case study. [27,31,32]. To prepare the flood-prone map, the initial step is to acquire the relevant data and to construct a spatial geodatabase.…”
Section: Study Area and Spatial Datamentioning
confidence: 99%